Media Use and the Cancer Communication Strategies of Cancer Survivors - Yoon, Heesoo; Sohn, Minsung; Jung, Minsoo (Journal of cancer prevention, 2016)
Communication related to health not only substantially affects perceptions and behaviors related to health but is also positively associated with the extent of health-information seeking and the practice of preventive behavior. Despite the fact that the number of cancer survivors has increased dramatically, there are few studies of the lack of health information, factors which act as barriers, and the difficulties in follow-up care experienced by cancer survivors. Therefore, we reviewed media utilization and the types of media used by cancer survivors with regard to risk communication and suggested appropriate strategies for cancer communication. According to the results, health communication contributed to health promotion by providing health-related information, consolidating social support factors such as social solidarity and trust, and reducing anxiety. In particular, participatory health communication may establish preventive programs which reflect the needs of communities, expand accessibility to better quality healthcare, and intensify healthy living by reducing health inequalities. Therefore, when people do not have an intention to obtain cancer screening, we need to intervene to change their behavior, norms, and degrees of self-efficacy. The findings of this study may help those involved in building partnerships by assisting in their efforts to understand and communicate with the public.